Morphometry of Rhinomugil Corsula (Hamilton, 1822) From Sitakunda Coast of the Bay of Bengal, Bangladesh (Bangladesh Journal of Zoology, 2021)
A total of 65 specimens of Rhinomugil corsula (Hamilton, 1822), measuring from 8.1 cm to 28.9 cm in total length, collected from the Sitakunda coast of the Bay of Bengal, were used for the morphometric analysis during the period between March 2016 and February 2018. Twenty seven morphometric characters were selected and studied during the investigation period. The regression equations – both arithmetic and logarithmic – between the total length (TL) and 21 morphometric characters, and head length (HL) with five morphometric characters related to the head, were determined. The value of coefficient of correlation ‘r’ for each relationship was calculated and t-test for each ‘r’ value was also done. The relationships of the various measurements of the body with the total length – and head length with the five relevant characters -of R. corsula from the Sitakunda coast of the Bay of Bengal showed linear relationships, which were highly significant (P0.01) with typical value b=1 indicating isometric relationships among the characters.Bangladesh J. Zool. 49 (2): 229-241, 2021